Real-world practices of hormone monitoring during ovarian stimulation in assisted reproductive technology: a global online survey - Sachs-Guedj, Noemie; Hart, Roger; Requena, Antonio; Vergara, Vanessa; Polyzos, Nikolaos P. (Frontiers in Endocrinology, 2023)
The aim of this study is to understand the global practice of routine hormonal monitoring (HM) during ovarian stimulation (OS) in the context of assisted reproductive technique (ART) treatment.Methods: An open-access questionnaire was available to 3,845 members of IVF-Worldwide.com from September 8 to October 13, 2021. The survey comprised 25 multiple-choice questions on when and how ultrasound (US) and hormone tests were conducted during ovarian stimulation OS. For most questions, respondents were required to select a single option. Some questions allowed the selection of multiple options.Results: In all, 528 (13.7%) members from 88 countries responded to the questionnaire. Most respondents (98.9%) reported using US to monitor OS cycles. HM was used by 79.5% of respondents during any of the cycle monitoring visits and was most commonly performed on the day of, or a day prior to final oocyte maturation. Overall, 87% of respondents claimed adjusting the dose of gonadotropin during OS, with 61.7% adjusting the dose based on hormonal levels. Oestradiol (E2) was the most frequently monitored hormone during all visits and was used by 74% of respondents for the prediction of ovarian hyperstimulation syndrome (OHSS). On or a day prior to ovulation triggering (OT), the number of respondents who measured progesterone increased from 34.3% in the second/third visit to 67.7%. Approximately one-third of respondents measured luteinizing hormone during all visits.Conclusions: Globally, most ART specialists (~80%) use HM, along with US, for monitoring OS, especially for the prevention of OHSS.